Impact of the addition of new vaccines in the early childhood schedule on vaccine coverage by 24 months of age from 2006 to 2016 in Quebec, Canada. Issue 29 (5th July 2018) - Kiely, Marilou; Boulianne, Nicole; Talbot, Denis; Ouakki, Manale; Guay, Maryse; Landry, Monique; Zafack, Joseline; Sauvageau, Chantal; De Serres, Gaston
Abstract: Context: Between 2004 and 2016, in the province of Quebec (Canada), 4 new antigens were added in the early childhood vaccine schedule from birth to 18 months, increasing the number of injections or doses needed from 7 to 12. These additions may have decreased the proportion of children who had received all recommended vaccines. Objectives: To assess the impact of the introduction of new vaccines to the childhood schedule on the 24-month vaccine coverage from 2006 to 2016 and identify factors associated with incomplete vaccination status by 24 months of age. Methods: We used the data from six cross-sectional vaccine coverage surveys conducted every two years which included a total of 3515 children aged 2 years old and randomly selected from the Quebec public health insurance database. Factors associated with an incomplete vaccine status by 24 months were identified with multivariable logistic regression. Results: Despite the addition of 4 new vaccine antigens since 2004, the vaccine coverage remained high from 2006 (82.4%) through 2016 (88.3%) for vaccines present in the schedule since 2006. In 2016, vaccine coverage was 78.2% for all vaccines included in the schedule. The vaccine coverage of new vaccines increases rapidly within 2 years of their introduction. For both new and older vaccines, incomplete vaccine status by 24 months of age is associated with a delay of 30 days or more in receiving the vaccines scheduled at 2 and 12 months of age. Conclusions: Increasing to 12 the number of doses in the recommended schedule has slightly reduced the vaccine coverage by 24 months of age and the vaccine coverage of vaccines already in the schedule remained stable over the years. Future additions to the vaccine schedule may not be similarly accepted by the population and this will require continuing the monitoring of vaccine coverage.